Amplitude and phase noise in two-membrane cavity optomechanics - Marzioni, Francesco; Rasponi, Francesco; Piergentili, Paolo; Natali, Riccardo; Di Giuseppe, Giovanni; Vitali, David (Frontiers in Physics, 2023)
Cavity optomechanics is a suitable field to explore quantum effects on macroscopic objects, and to develop quantum technologies applications. A perfect control on the laser noises is required to operate the system in such extreme conditions, necessary to reach the quantum regime. In this paper we consider a Fabry-Perót cavity, driven by two laser fields, with two partially reflective SiN membranes inside it. We describe the effects of amplitude and phase noise on the laser introducing two additional noise terms in the Langevin equations of the system's dynamics.Experimentally, we add an artificial source of noise on the laser. We calibrate the intensity of the noise we inject into the system, and we check the validity of the theoretical model. This procedure provides an accurate description of the effects of a noisy laser in the optomechanical setup, and it allows to quantify the amount of noise.